An analysis of the legal framework for domestic violence against old age people in India - Ansari, Faiz Ayat (Addiction & criminology, 2024)
The growing problem of domestic violence against older adults in India demands an immediate and comprehensive response. This paper critically analyzes the current legal framework to assess its effectiveness in protecting this vulnerable population from abuse. Existing legislation offers fragmented and limited protection. While criminal provisions address physical violence, psychological, economic, and sexual abuse often fall through the cracks. The paper delves into these gaps, highlighting the lack of a specific definition of "elder abuse" and the inadequacy of remedies for non-physical forms of violence. Furthermore, the paper examines societal challenges hindering access to justice. Stigma against reporting abuse, dependence on perpetrators for basic needs, and the complex dynamics of family relationships often deter older adults from seeking legal redress. The paper investigates these aspects, emphasizing the need for sensitizing law enforcement and judicial personnel to effectively handle elder abuse cases. Further exploration focuses on innovative legal remedies adopted in other countries, such as restraining orders and specialized elder abuse courts. Drawing insights from these models, the paper proposes potential reforms to strengthen the Indian legal framework. This includes advocating for a comprehensive elder abuse legislation, streamlined reporting procedures, and accessible support systems for victims. Ultimately, the paper seeks to bridge the gap between existing legal provisions and their implementation in reality. By analyzing the shortcomings of the current framework and proposing proactive solutions, it aims to pave the way for a more effective legal response to domestic violence against older adults in India.